A validated numerical model for predicting the in-plane seismic response of lightly reinforced, low-aspect ratio reinforced concrete shear walls. (1st August 2018) - Epackachi, Siamak; Whittaker, Andrew S.
Highlights: Development of a finite element model in LS-DYNA to simulate the response of RC walls. Validation of the developed finite element model using data from 22 wall specimens. Considering the effect of restrained shrinkage on the initial stiffness of RC walls. Considering the effect of concrete crushing on the post-peak strength of RC walls. Parametric study to investigate the effects of design parameters on monotonic response. Abstract: A finite element model is developed in LS-DYNA to simulate the in-plane cyclic behavior of lightly reinforced, low-aspect ratio reinforced concrete (RC) shear walls. Data from tests of 22 low-aspect ratio RC shear walls in three laboratories are used to validate the numerical model. The design variables in the testing programs included aspect ratio, day-of-test concrete compressive strength, vertical and horizontal web reinforcement ratio, reinforcement ratio in boundary elements, and yield and ultimate strengths of reinforcement, and these are addressed in the numerical model. The finite element predictions and test results, including the force–displacement relationships and damage to the RC shear walls, are presented and contrasted. Numerical methods are proposed to model the effect of early stage cracking on the initial stiffness of RC walls and to capture post-peak strength degradation. The numerical simulations are in good agreement with the measured responses. The validated LS-DYNA model is used in a parametric study to investigate the effects of wall aspect ratio, reinforcement ratios in web and boundary elements, and compressive axial load on the monotonic response of RC walls. The accuracy of four equations used to predict the peak shear strength of low-aspect ratio walls is assessed using results of the numerical analyses.